Theoretical aspects of life-cycle personal finances management - Daiva Jurevičienė; Aušra Klimavičienė (Business: Theory and Practice, 2008)
The article examines the theoretical aspects of personal finances management. The article reveals the concept of financial assets and investments, and the scope of personal finances management. Various authors’ approaches to finance planning process are discussed. The links between person’s life cycle and investments are investigated. Life-cycle finance widely analyzed by foreign scientists is introduced in the article. Authors indicate necessary prospective researches in the area of personal finances management.